Assessment of Clinical Efficiency of Manual K files, Kedo-S Plus and Fanta AFTM Pediatric Rotary Files During Pulp Therapy of Primary Teeth: A Clinical Trial (Academia Journal of Medicine, 2024)
The objective is to evaluate the instrumentation time required  for primary molar root canal preparation using two pediatric  rotary file systems (Kedo-S Plus & Fanta AFTM Baby) in  comparison to manual K-files.  60 lower primary molars of healthy youngsters, ages 4-8 years  were participated. Three groups (n=20) received a random  assignment of molars. Kedo-S Plus and Fanta AFTM Baby rotary  systems were used to prepare groups I and II, while a manual K file was used to organise group III, stopwatch was used to  estimate the instrumentation time. The result shows that the  78.8 seconds),  followed by group II and the manual-K file group (p
Keywords: Pulpectomy; Deciduous tooth; Rotary files